THE ORETICAL AND SCIENTIFIC APPROACHES TO ENSURING THE QUALITY OF EDUCATION IN THE TRAINING OF COMPETITIVE PERSONNEL IN HIGHER EDUCATIONAL INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the scientific and theoretical basis oftraining competitive personnel in higher education, the essence of developing a strong staff to improve the quality of education.